MEDICAL AND ORGANIZATIONAL BASES OF BREAST MILK BANK FUNCTIONING - I. A. Belyaeva; E. P. Bombardirova (Вопросы современной педиатрии)
The article deals with problems of development and functioning of breast milk bank, substantiation of necessity of such institution, peculiarities of collection, processing and storing of donor breast milk.